Annealing effects on deuterium retention behavior in damaged tungsten. (December 2016) - Sakurada, S.; Yuyama, K.; Uemura, Y.; Fujita, H.; Hu, C.; Toyama, T.; Yoshida, N.; Hinoki, T.; Kondo, S.; Shimada, M.; Buchenauer, D.; Chikada, T.; et al.
Highlights: W samples were irradiated with 6.0 MeV Fe 2+ at room temperature and 6.4 MeV Fe 3+ at elevating temperature. D retention in W irradiated at elevating temperature was reduced as compared to that in annealed W after Fe 2+ irradiation. D desorption behaviors were almost same in both W sample annealed at ≥1173 K under/after irradiation. Abstract: Effects of annealing after/under iron (Fe) ion irradiation on deuterium (D) retention behavior in tungsten (W) were studied. The D2 TDS spectra as a function of heating temperature for 0.1 dpa damaged W showed that the D retention was clearly decreased as the annealing temperature was increased. In particular, the desorption of D trapped by voids was largely reduced by annealing at 1173 K. The TEM observation indicated that the size of dislocation loops was clearly grown, and its density was decreased by the annealing above 573 K. After annealing at 1173 K, almost all the dislocation loops were recovered. The results of positron annihilation spectroscopy suggested that the density of vacancy-type defects such as voids, was decreased as the annealing temperature was increased, while its size was increased, indicating that the D retention was reduced by the recovery of the voids. Furthermore, it was found that the desorption temperature of D trapped by the voids for damaged W above 0.3 dpa was shifted toward higher temperature side. These results lead to a conclusion that the D retention behavior is controlled by defect density. The D retention in the samples annealed during irradiation was less than that annealed after irradiation. This result shows that defects would be quickly annihilated before stabilization by annealing during irradiation.